Opportunities and Challenges of Contract Farming in India: A Quantitative Investigation - SRIVASTAV, SHASHANK (International Journal of Psychosocial Rehabilitation, 2024)
Contract farming has emerged as a potential tool for improving agricultural productivity and enhancing farmers' incomes in India. The research can explore how contract farming has led to increased adoption of new technologies, improved access to credit and markets, and higher incomes for contract farmers. However, challenges such as lack of transparency, inadequate extension services, and limited bargaining power of farmers were also identified. The study concludes by suggesting policy interventions to address these challenges and enhance the possible profits of contract farming for farmers in India. Overall, the research contributes to the existing studies on contract farming in developing countries by providing evidence on the many opportunities and many challenges of contract farming in India.